FAO-56 penman-monteith daily e T o from linear regression calibrated hargreaves equation with wind terms in tropics with limited data - Kra, E. (International Journal of Agronomy, 2014)
Hargreaves equation (HG), which lacks a wind speed (u 2) term, was modified, through a linear regression calibration method, into LHGu which has u 2 terms. LHGu is effectively a simplified method for approximating FAO-56 Penman-Monteith equation (FPM) daily reference evapotranspiration (E T o) in tropics with only temperature data. In LHGu, the "0.0023" constant term in HG was calibrated as a shifted power function of u 2, and the calibration constant was parametrized as a quadratic function of u 2. LHGu was developed using simulated constant u 2 data and historical temperature data for four sites in West Africa: Abidjan, Accra, Daloa, and Lome. LHGu matched FPM E T o better than HG over a wide range of u 2: for Accra, for u 2 range 0.5-6.0 m/s, the modified coefficient of efficiency, E 1, varied narrowly (0.83-0.98) for LHGu but widely (0.14-0.95) for HG optimized for u 2 = 2.0 m/s; the corresponding MBE ranges were -0.05-0.01 mm/d for LHGu and 0.02-0.63 mm/d for HG which cannot respond to varying daily u 2. LHGu is useful for quickly computing practically accurate estimates of FPM E T o for varying daily u 2 where only temperature data are available. © 2014 Eric Kra.